2013
DOI: 10.1002/jez.b.22501
|View full text |Cite
|
Sign up to set email alerts
|

Soldier Morphogenesis in the Damp‐Wood Termite Is Regulated by the Insulin Signaling Pathway

Abstract: Eusocial insects exhibit various morphological castes associated with the division of labor within a colony. Termite soldiers possess defensive traits including mandibles that are greatly exaggerated and enlarged, as compared to termite reproductives and workers. The enlarged mandibles of soldiers are known to result from dynamic morphogenesis during soldier differentiation that can be induced by juvenile hormone and its analogs. However, the detailed developmental mechanisms still remain unresolved. Because t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 80 publications
(108 reference statements)
2
41
0
Order By: Relevance
“…takasagoensis have reduced mandibles and enlarged frontal glands which they use to spray chemicals against enemies. Importantly, manipulation experiments for studying caste differentiation, such as hormone application and RNA interference techniques, have been established in these species (for example, Ogino et al [19] and Hattori et al [20] for H . sjostedti , Tsuchiya et al [21] and Nambu et al [22] for R .…”
Section: Introductionmentioning
confidence: 99%
“…takasagoensis have reduced mandibles and enlarged frontal glands which they use to spray chemicals against enemies. Importantly, manipulation experiments for studying caste differentiation, such as hormone application and RNA interference techniques, have been established in these species (for example, Ogino et al [19] and Hattori et al [20] for H . sjostedti , Tsuchiya et al [21] and Nambu et al [22] for R .…”
Section: Introductionmentioning
confidence: 99%
“…Termite orthologs of the IIS pathway, including HsjInR, HsjPKB/Akt, were up-regulated during soldier morphogenesis 130 . It is believed that insulin signaling could interact with JH and may play an important role in mandible elongat i on during soldier formation 130.…”
Section: Regulation Of Soldier Caste Differentiationmentioning
confidence: 95%
“…Recently, it has been demonstrated that soldier morphogenesis is associated with the insulin/insulin-like growth factor signaling (IIS) pathway in the termite H. sjostedti 130. Termite orthologs of the IIS pathway, including HsjInR, HsjPKB/Akt, were up-regulated during soldier morphogenesis 130 .…”
Section: Regulation Of Soldier Caste Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, JH titers in workers might be suppressed to lower levels by the presence of soldiers (Figure 5D). Since the social interactions are suggested to affect the expression patterns of genes that were shown to regulate the soldier-specific morphogenesis (Koshikawa et al, 2002, 2003, 2005, 2010; Hattori et al, 2013; Toga et al, 2012, 2013), the relationships between those gene expression patterns and social interactions will be clarified sooner or later.…”
Section: Juvenile Hormone—an Endocrine Mediator Between the Social Inmentioning
confidence: 99%